Multifaceted impacts of sustainable land management in drylands: a review. - Marques, M.J.; Schwilch, G.; Lauterburg, N.; Crittenden, S.; Tesfai, M.; Stolte, J.; Zdruli, P.; Doko, A.; Zucca, C.; Petursdottir, T.; Evelpidou, N.; Karkani, A.; et al. (Sustainability, 2016)
Biophysical restoration or rehabilitation measures of land have demonstrated to be effective in many scientific projects and small-scale environmental experiments. However circumstances such as poverty, weak policies, or inefficient scientific knowledge transmission can hinder the effective upscaling of land restoration and the long term maintenance of proven sustainable use of soil and water. This may be especially worrisome in lands with harsh environmental conditions. This review covers recent efforts in landscape restoration and rehabilitation with a functional perspective aiming to simultaneously achieve ecosystem sustainability, economic efficiency, and social wellbeing. Water management and rehabilitation of ecosystem services in croplands, rangelands, forests, and coastlands are reviewed. The joint analysis of such diverse ecosystems provides a wide perspective to determine: (i) multifaceted impacts on biophysical and socio-economic factors; and (ii) elements influencing effective upscaling of sustainable land management practices. One conclusion can be highlighted: voluntary adoption is based on different pillars, i.e. external material and economic support, and spread of success information at the local scale to demonstrate the multidimensional benefits of sustainable land management. For the successful upscaling of land management, more attention must be paid to the social system from the first involvement stage, up to the long term maintenance.